Effectiveness of Essence of Chicken in Improving Cognitive Function in Young People Under Work-Related Stress: A Randomized Double-Blind Trial. Issue 19 (May 2016) - Chan, Lung; Wang, Hsuan-Min; Chen, Kuan-Yu; Lin, Ying-Chin; Wu, Pei-Jung; Hsieh, Wan-Lin; Chen, Ying-Ru; Liu, Cheung-Pin; Tsai, Han-Yin; Chen, Yun-Ru; Chang, Hsiu-Hui; Hsieh, Yi-Chen; et al.
Abstract : Abstract: Work-related stress (WS) can result in considerable and extensive changes in physiological and psychological performance. WS beyond the optimal levels induces anxiety, confusion, exhaustion, and burnout. Chronic WS affects neurocognitive performance, particularly attention and visuospatial memory. Essence of chicken (EC) has been reported to improve neurocognitive function after mental stress. To investigate the beneficial effects of EC in improving neurocognitive performance under WS, we conducted a randomized, double blind trial. Total 102 young workers in New Taipei City with high WS, evaluated using the Individual Subjective Perception Job Stress Scale scores (>36 for job leaders and 33 for nonleaders) were recruited. Fifty-one participants received 70 mL of EC and 51 received a placebo daily for 2 weeks. Blood tests and neurocognitive assessment were performed before treatment, at the end of treatment, and 2 weeks after treatment. EC improved the performance of participants with high depression scores in the form-color associative memory test, used for assessing short-term memory. Although creatinine and glutamic-pyruvic transaminase (GPT) levels increased in week 2, but the levels returned to the baseline in week 4. Blood urea nitrogen (BUN) levels decreased in week 4. EC significantly improved short-term memory in participants with high WS and concomitant depressive mood, although it slightly increased GPT and creatinine levels and reduced BUN levels. The long-term treatment effects of EC warrant further investigation.